DrosophilaZIP13 over‐expression or transferrin1 RNAi influences the muscle degeneration of Pink1 RNAi by elevating iron levels in mitochondria. Issue 5 (5th February 2022) - Xue, Jinsong; Li, Guangying; Ji, Xiaowen; Liu, Zhi‐ Hua; Wang, Hui‐ Li; Xiao, Guiran
Abstract: Disruption of iron homeostasis in the brain of Parkinson's disease (PD) patients has been reported for many years, but the underlying mechanisms remain unclear. To investigate iron metabolism genes related to PTEN‐induced kinase 1 ( Pink1 ) and parkin (E3 ubiquitin ligase), two PD‐associated proteins that function to coordinate mitochondrial turnover via induction of selective mitophagy, we conducted a genetic screen in Drosophila and found that altered expression of genes involved in iron metabolism, such as Drosophila ZIP13 ( dZIP13 ) or transferrin1 ( Tsf1 ), significantly influences the disease progression related to Pink1 but not parkin . Several phenotypes of Pink1 mutant and Pink1 RNAi but not parkin mutant were significantly rescued by over‐expression (OE) of dZIP13 ( dZIP13 OE) or silencing of Tsf1 ( Tsf1 RNAi) in the flight muscles. The rescue effects of dZIP13 OE or Tsf1 RNAi were not exerted through mitochondrial disruption or mitophagy; instead, the iron levels in mitochondira were significantly increased, resulting in enhanced activities of enzymes participating in respiration and increased ATP synthesis. Consistently, the rescue effects of dZIP13 OE or Tsf1 RNAi on Pink1 RNAi can be inhibited by decreasing the iron levels in mitochondria through mitoferrin ( dmfrn ) RNAi. This study suggests that dZIP13, Tsf1, and dmfrn might act independently of parkin in a parallel pathway downstream of Pink1 by modulating respiration and indicates that manipulation of iron levels in mitochondria may provide a novel therapeutic strategy for PD associated with Pink1 . Abstract : Elevating mitochondrial iron levels could restore PTEN‐induced kinase 1 ( Pink1 ) RNAi phenotypes in Drosophila melanogaster . (a) Pink1 down‐regulation results in mitochondrial aggregation. Mitochondria complexes activities and electron transport chain (ETC) process are predominantly decreased. (b) Drosophila ZIP13 over‐expression ( dZIP13 OE) or transferrin1 ( Tsf1 ) RNAi alleviate Pink1 ‐deficient injury via increased iron level in mitochondria, therefore enhance electron transfer chain (ETC), and extenuate mitochondria dysfunction and Parkinson's disease (PD) phenotypes. These findings indicated that manipulation of iron levels in mitochondria may provide a novel therapeutic strategy for PD associated with Pink1 .